A Discovery or a Misery? The Issuance of Anti-Suit Injunction before WTO - Besar, Besar; Zaki, Muhammad Reza Syariffudin; Tanjaya, Steven; Koos, Stefan; Sabilil, Maria Nauli Salsabilah (Faculty of Law, Universitas Brawijaya, 2023)
On 27 January 2023, the Dispute Settlement Body established a panel as requested by the European Union in document WT/DS611/5, pursuant to Article 6 of the Understanding on Rules and Procedures Governing the Settlement of Disputes. In fact, the European Union has proposed the formation of a panel according to Article 6 of the Dispute Settlement Understanding (DSU) to respond to the Action against China's lawsuit against high technology in the European Union. China imposed a preservation measure, Anti-Suit Injunction (ASI), that prohibit patent holder for asserting their rights before non-Chinese courts. Such movement is inconsistent to international principles, namely National Treatment (NT) and Most-Favored-Nation (MFN). As the EU claimed China on the subject of patent use on high technology, this discussion will further dissect the WTO Agreement on the Trade-Related Aspects of Intellectual Property Rights (TRIPS). Specifically, Article 3 on National Treatment and Article 4 on Most-Favored-Nation Treatment. The issuance of ASI itself is not listed under Appendix 1 of the DSU that regulates laws that are applicable and recognized as WTO norms under a WTO panel. The WTO panel has never adjudicated any cases relating to the issuance of ASI. This questions whether a WTO norm will be formed before the WTO panel and whether or not China has violated the principles of the WTO and the TRIPS Agreement.